A ppm level Rh-based composite as an ecofriendly catalyst for transfer hydrogenation of nitriles: triple guarantee of selectivity for primary amines. Issue 6 (30th January 2019) - Liu, Lei; Li, Jifan; Ai, Yongjian; Liu, Yuhong; Xiong, Jialiang; Wang, Hongdong; Qiao, Yijun; Liu, Wenrui; Tan, Shanchao; Feng, Shaofei; Wang, Kunpeng; Sun, Hongbin; et al.
Abstract : A 49 ppm Rh catalyst selectively transforms nitriles into primary amines with economical HCOOH and exhibits a TOF value of 6803 h −1 . Abstract : Hydrogenation of nitriles to afford amines under mild conditions is a challenging task with an inexpensive heterogeneous catalyst, and it is even more difficult to obtain primary amines selectively because of the accompanying self-coupling side reactions. An efficient catalytic system was designed as Fe3 O4 @nSiO2 –NH2 –RhCu@mSiO2 to prepare primary amines through the transfer hydrogenation of nitrile compounds with economical HCOOH as the hydrogen donor. The loading of rhodium in the catalyst could be at the ppm level, and the TOF reaches 6803 h −1 for Rh. This catalytic system has a wide substrate range including some nitriles that could not proceed in the previous literature. The experimental results demonstrate that the excellent selectivity for primary amines is guaranteed by three tactics, which are the strong active site, the inhibition of side products by the hydrogen source and the special pore structure of the catalyst. In addition, the catalyst could be reused ten times without activity loss through convenient magnetic recovery.